2006
DOI: 10.1073/pnas.0602413103
|View full text |Cite
|
Sign up to set email alerts
|

Olefin metathesis and quadruple hydrogen bonding: A powerful combination in multistep supramolecular synthesis

Abstract: We show that combining concepts generally used in covalent organic synthesis such as retrosynthetic analysis and the use of protecting groups, and applying them to the self-assembly of polymeric building blocks in multiple steps, results in a powerful strategy for the self-assembly of dynamic materials with a high level of architectural control. We present a highly efficient synthesis of bifunctional telechelic polymers by ring-opening metathesis polymerization (ROMP) with complementary quadruple hydrogen-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 38 publications
1
66
0
1
Order By: Relevance
“…The polymers themselves often have broad molecular weight distributions or high T g s, necessitating melt annealing at temperatures high enough to significantly reduce the strength of the hydrogen bond. Despite these limitations, the incorporation of both homocomplementary 3,4,6,19 and heterocomplementary 14,16,[20][21][22][23][24] MHB groups at polymer chain ends has been previously demonstrated. In particular, the work of Mather et al 21 first demonstrated the incorporation of MHB chain ends through the use of controlled radical polymerization from uracilfunctional nitroxide initiators.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers themselves often have broad molecular weight distributions or high T g s, necessitating melt annealing at temperatures high enough to significantly reduce the strength of the hydrogen bond. Despite these limitations, the incorporation of both homocomplementary 3,4,6,19 and heterocomplementary 14,16,[20][21][22][23][24] MHB groups at polymer chain ends has been previously demonstrated. In particular, the work of Mather et al 21 first demonstrated the incorporation of MHB chain ends through the use of controlled radical polymerization from uracilfunctional nitroxide initiators.…”
Section: Introductionmentioning
confidence: 99%
“…19 The nature of the interaction varies widely and most commonly consists of either metal-ligand, 20,21 ionic, 22,23 or hydrogen bonding. 24,25 Incorporation of these into various macromolecular architectures such as diblock, [26][27][28][29][30][31][32][33][34][35] triblock, [36][37][38] multiblock, [39][40][41] star 42 and graft copolymers, [43][44][45] blends, 35,46 and gels 47,48 has resulted in remarkably simple thermal control over the polymer structure and related properties.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have also received much attention as fundamental synthetic building blocks because of their hydrogen bonding and π-π stacking potential. In particular, Meijer's ureidopyrimidone (UPy) building block [9,10], with its characteristics of a high dimerization constant and synthetic accessibility, has found widespread applications in supramolecular chemistry, materials science, and catalysis [11,12]. Zimmerman's ureidodeazapterin and ureidonaphthyridine modules are also successful examples of heterocyclic building blocks [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%